Evaluation of smear layer removal and micro hardness alteration of radicular dentin after using various chelating agents - An atomic force microscopic study - Mounika Veeraiyan; Yata Prashanth Kumar; Chikine Yashas Chandhar; Yeligati Priyanka; Manisha Jaiswal; Deepika Kemasaram (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: For endodontic therapy to be successful, the smear layer produced by the root canal instruments must be removed. The study's objective is to evaluate the effectiveness of radicular dentin microhardness modification and smear layer removal utilizing various chelating agents. Materials and Methods: Extracted human mandibular single-rooted premolar teeth were selected for the study. The specimens were sectioned to obtain a standard root length and, working length determination was done. Cleaning and shaping were done in all the samples till the size F3 (Protaper universal). Based on the chelating agents using samples were randomly divided into four groups, Group-I: Saline (negative control), Group-II: 17% EDTA (DeSmear, Ahmedabad, Gujarat) (positive control), Group-III: 0.2% Chitosan (Everest-Biotech, Bengaluru), Group-IV: 20% N-Acetyl cysteine (NAC) (Sisco Research Laboratories, Mumbai), Group-V: 5% Pentetic acid (New Alliance Fine chem Pvt Ltd, Mumbai). All the samples were prepared for smear layer removal and surface roughness evaluation using an atomic force microscope. Results: It was observed that significantly (P = 0.000) the mean roughness average was higher among group II EDTA (148 ± 8.5) followed by group III 0.2% Chitosan (92.5 ± 3.42), group IV 20% NAC (85.2 ± 2.17), and group V 5% Pentetic acid (73.3 ± 3.39) and least by group I Saline (59.3 ± 3.31). The highest smear layer removal was seen with group II (EDTA) followed by group III (0.2% Chitosan), group IV (20% NAC), and group V (Pentetic acid). Conclusion: All the chelating agents removed smear layer in coronal third, middle third whereas none of them were able to entirely eliminate from the apical third. Chitosan with smear layer removal capacity equal to EDTA with limited roughness can be considered as a valid alternative as final irrigant.